Evolução do crédito consignado no estado do Rio Grande do Sul : aplicação da metodologia de Box & Jenkins - Rech, Munique (My University, 2018)
After the implementation of the Real Plan, with the change brought about by inflationary stabilization, Brazil presented an increase in the supply of bank credit, as a strategy for banks to maintain the level of their revenues. However, the country still needs to expand its credit supply, as it has a credit-to-GDP ratio of 62.2%, lower than the average for all countries, of 131.7% (WORLD BANK, 2017). The Brazilian financial system is predominantly banking, and the provision of credit comes mainly from banking institutions. The resources obtained through bank credit return to society, in the form of consumption and investments, contributing to economic activity. In addition to this social aspect, credit lending makes banks profitable, impacting the financial performance of these institutions. Following the enactment of the law that allowed for the payroll deductible loan, which is characterized by the debit of the loan installments directly on the payroll of the debtors, the banks expanded the credit offer, since this type of loan made possible a reduction in defaults, reducing the credit risk. In view of the above, the objective of the study was to find a model that represents the behavior of the evolution of payroll loans with a financial institution, assisting in its strategy by predicting this variable. The study was conducted through a quantitative research, with secondary data provided by the financial institution. The statistical treatment of the data was performed through the analysis of time series, using the methodology proposed by Box & Jenkins, using the software R Studio. The result was an ARIMA model (0, 2, 1), which represented the behavior of the evolution of payroll loans with the financial institution, with analysis of 96 monthly observations, from January 2009 to December 2016. With the model, the forecast for six months, from January to June 2017. The maximum difference between the expected value and the actual value of the variable was 1.57%, which attests to the accuracy of the model found. Therefore, as a theoretical result, it was evidenced that the ARIMA model was adequate for the prediction of payroll loans granted by the financial institution. As an empirical result, the predictive model found can act as a strategic tool for the financial institution, since its application can contribute to the process of determining competitive strategies.
Após a implantação do Plano Real, com a mudança ocasionada pela estabilização inflacionária, o Brasil apresentou ampliação na oferta de crédito bancário, como estratégia dos bancos para manterem o nível das suas receitas. Porém, o país ainda necessita ampliar o fornecimento de crédito, pois apresenta uma relação crédito/PIB de 62,2%, inferior à apresentada pela média de todos os países, de 131,7% (BANCO MUNDIAL, 2017). O sistema financeiro brasileiro é predominantemente bancário, e o fornecimento de crédito advém principalmente de instituições bancárias. Os recursos obtidos através do crédito bancário retornam para a sociedade, em forma de consumo e investimentos, contribuindo com a atividade econômica. Além desse cunho social, a concessão de crédito rentabiliza os bancos, impactando no desempenho financeiro dessas instituições. A partir da sanção da lei que permitiu a concessão do crédito consignado, que se caracteriza pelo débito das parcelas do empréstimo diretamente na folha de pagamento dos devedores, os bancos ampliaram a oferta de crédito, uma vez que essa modalidade de empréstimo possibilitou uma redução na inadimplência, diminuindo o risco atrelado ao crédito. Diante do exposto, o objetivo do estudo foi encontrar um modelo que represente o comportamento da evolução do crédito consignado junto a uma instituição financeira, auxiliando na sua estratégia através da previsão dessa variável. O estudo foi realizado através de uma pesquisa quantitativa, com dados secundários fornecidos pela instituição financeira. O tratamento estatístico dos dados foi realizado através da análise de séries temporais, por meio da metodologia proposta por Box & Jenkins, com a utilização do software R Studio. O resultado encontrado foi um modelo ARIMA (0, 2, 1), que representou o comportamento da evolução do crédito consignado junto à instituição financeira, com análise de 96 observações mensais, de janeiro de 2009 a dezembro de 2016. Com o modelo, realizou-se a previsão para seis meses, de janeiro a junho de 2017. A diferença máxima entre o valor previsto e o valor real da variável foi de 1,57%, o que atesta a acuracidade do modelo encontrado. Por conseguinte, como resultado teórico, evidenciou-se que o modelo ARIMA revelou-se adequado para a previsão do crédito consignado concedido pela instituição financeira. Como resultado empírico, o modelo de previsão encontrado pode atuar como ferramenta estratégica para a instituição financeira, uma vez que a sua aplicação pode colaborar com o processo de determinação de estratégias competitivas.
Keywords: Empréstimos bancários; Bancos; Concorrência; Rio Grande do Sul; Bank loans; Banks and banking; Competition; Rio Grande do Sul, Brazil